2010
DOI: 10.1021/jp103026q
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Effects on the Hole States of Triisopropylsilylethynyl-Substituted Oligoacenes

Abstract: The effects of intermolecular interactions on the electronic properties of bis-triisopropylsilylethynyl-substituted (TIPS) anthracene, tetracene, and pentacene are obtained from comparison of the ionization energies measured by solid-phase ultraviolet photoelectron spectroscopy (UPS) with the ionization energies measured by gas-phase UPS, and with the oxidation potentials measured electrochemically in solution. Additional insight is provided by electronic structure calculations at the density functional theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 44 publications
(103 reference statements)
4
32
0
Order By: Relevance
“…The results were provent o be fabricated and later had to be retracted. [10,11] Both the high charge-carrier mobility [10,11] and the HOMO-LUMO gap [19][20][21][22][23] suggest applications for acenes as possible "successors to traditional inorganic semiconductors." [10,11] Both the high charge-carrier mobility [10,11] and the HOMO-LUMO gap [19][20][21][22][23] suggest applications for acenes as possible "successors to traditional inorganic semiconductors."…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results were provent o be fabricated and later had to be retracted. [10,11] Both the high charge-carrier mobility [10,11] and the HOMO-LUMO gap [19][20][21][22][23] suggest applications for acenes as possible "successors to traditional inorganic semiconductors." [10,11] Both the high charge-carrier mobility [10,11] and the HOMO-LUMO gap [19][20][21][22][23] suggest applications for acenes as possible "successors to traditional inorganic semiconductors."…”
Section: Introductionmentioning
confidence: 99%
“…[21] Usually onset potentials of oxidation andr eduction, [34] differential pulse voltammetric peak potentials, [20][21][22] or formal potentials E 0 derived from cyclic voltammetric peak potentials [33,34,49] are the basic information. Analysis of the relationship between ultraviolet photoelectrons pectroscopic ionization energies and electrochemical potentials indicated the effects of various internal and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the physical interpretation of these measurements can remain controversial. 11 To take a recent example involving two widely studied organic semiconductors, the IE of the pentacene crystal has been measured by the Lichtenberger group to be 4.81 eV 12,13 , which is 0.24 eV smaller than the IE measured by the Kahn group (5.05 eV) 14,15 ; on the other hand, the IE of tri-isopropylsilylethynyl (TIPS)-pentacene determined by the Lichtenberger group (5.84 eV) 12,13 is 0.80 eV larger than that reported by the Kahn group (5.04 eV) 14,15 . As a result, the solid-state polarization energies estimated for the TIPS-pentacene films are remarkably different: 0.44 eV by the Lichtenberger group vs. 1.24 eV by the Kahn group.…”
mentioning
confidence: 99%
“…We note that Frisbie and co-workers have recently elucidated the tunneling transport in molecular junctions based on oligoacenes and concluded that oligoacenes, serving as molecular wires for nanosized electronic devices, are more superior when compared with some typical π -conjugated oligomers such as polyacetylene, oligo(thiophene), oligo(meso-meso-linked zinc(II) porphyrin-butadiynylene), oligo( p -phenylethynylene) and oligo( p -phenylene)161718. Although oligoacene compounds have always been one of the favorites of theoretical researchers192021222324, the research efforts on such systems combining theory and experiment are still relatively limited mainly due to the synthetic challenge and the extreme instability of longer acenes, let alone the detailed and systematic comparison of their electronic transfer252627282930. Accordingly, a thorough understanding and regular exploration of their electronic transfer properties, from both an experimental and theoretical perspective is of great significance for the design and development of electronic devices intimately tied to oligoacenes.…”
mentioning
confidence: 99%